2012
DOI: 10.1103/physreva.85.011403
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy peak structure in strong-field ionization by midinfrared laser pulses: Two-dimensional focusing by the atomic potential

Abstract: We analyze the formation of the low-energy structure (LES) in above-threshold ionization spectra first observed by Quan et al. [1] and Blaga et al.[2] using both quasi-classical and quantum approaches. We show this structure to be largely classical in origin resulting from a two-dimensional focusing in the energy-angular momentum plane of the strong-field dynamics in the presence of the atomic potential. The peak at low energy is strongly correlated with high angular momenta of the photoelectron. Quantum simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 20 publications
2
80
2
Order By: Relevance
“…The fact that the CEP-fixed numerical results agree with the experimental ones, which can be interpreted as an average over the CEP due to the Gouy phase shift along the Gaussian laser focus is not obvious, especially considering the pronounced CEP dependence of the LES for short pulses [15,16].…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…The fact that the CEP-fixed numerical results agree with the experimental ones, which can be interpreted as an average over the CEP due to the Gouy phase shift along the Gaussian laser focus is not obvious, especially considering the pronounced CEP dependence of the LES for short pulses [15,16].…”
mentioning
confidence: 76%
“…However, the observation of new structures [10,11] in the electron spectrum at low energies posed a puzzle: reproduced by numerical solutions of the time-dependent Schrödinger equation as well as by classical simulations [11][12][13][14][15][16][17][18], these now called "low" [10] and "very-low" [13] energy structures (LES and VLES) evade the well established three-step model. Early numerical studies [11][12][13] clearly hinted the importance of the Coulomb potential from the parent ion during formation of the low energy structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10] It is widely believed that the high-energy electron is related to the rescattering (recollision) mechanism, [11] while the low-energy part is believed to originate in direct photo-ionization. To date, little research [12][13][14][15] has been reported on the intensity dependence of the low-energy structure (LES), especially for a detailed comparison of the current state-of-the-art theory and the experimental data.…”
Section: Introductionmentioning
confidence: 99%